Odkształcenia Powolne Betonu - Brandt, A.; Thiel, K. (Engineering Transactions, 1960)
This is a survey of modern theories and of results of investigations concerning the problem of slow deformations of concrete. This definition contains the shrinkage and swelling of unloaded concrete, described in Sec. 3, the creep under a load described in Sec. 4 and the thermal deformations not treated in the present paper. The word «slow» is used to distinguish the processes described from instant deformations appearing immediately after the load is applied. Volume changes of unloaded concrete start instantly after the concrete mixture is prepared. First, the rate of deformation is high, then it decreases under invariable external conditions and tends to stabilization. In Table 5 approximate values are presented, illustrating the shrinkage process in time and in Table 2 approximate data are given for total shrinkage deformations under various conditions. According to the hypotheses now in use, the shrinkage of concrete is connected with two processes: the drying of concrete and the hydration of cement. The drying of concrete results in changes of tension in capillaries partially filled with water and a gradual increase of the real stresses and strains of the rigid «framework» of concrete. The hydration of the anhydrous salts contained in the cement is connected with a reduction of the volume of cement mortar. The shrinkage and swelling processes is influenced by the curing conditions and the choice of components of the concrete. The concrete shrinks when drying out, and swells if water is absorbed from the ambient medium. The conditions of the initial period of concrete maturing are of particular importance, the shrinkage being of partially irreversible nature. In other cases, the concrete; independently of its age, is adjusted to the ambient conditions by absorbing or evaporating water and the volume changes involved. For the first 24 hours the shrinkage is represented at Fig. 2. This is a very important part of the process, observed and considered since recently. Before, the deformations were measured first after more than ten hours due to the difficulty of measuring fresh concrete mass. The shrinkage deformations increase with the quantity of cement and with the volume of water exceeding that necessary for the hydration process which has to be evaporated. An aggregate of low deformability and of carefully chosen grain size constitutes a rigid framework showing small deformations under the action of shrinkage stresses due to the cement mortar. Finally, a number of tentative forecasts of the process and the final values of shrinkage are given in Sec. 3. By the name of concrete creep we understand the difference between the total slow deformation and the shrinkage in a loaded concrete. The creep process has a character approaching that of shrinkage but the deformations grow more rapidly. Approximate values are collated in Table 6. The creep phenomena consists in concrete consolidation under load. First, the load is taken up by water and the «framework» of the concrete, but the stresses and strains in the framework grow progressively due to water filtration. As the share of water decreases the process becomes stabilized. The experimental relation between the shrinkage and the creep is not yet entirely explained although the dependence of these two phenomena is doubtless.. The decisive factor for creep is the way in which the concrete is loaded. Small stresses in the concrete do not cause creep. If they increase up to 50% of the strength of concrete the stress-strain relation has a linear character. Further increase of stress is connected with a rapid increase of retarded deformations. Concrete after a long curing period reaches sufficient strength and shows smaller creep than a younger one subjected to the same load. The creep decreases if more moisture is contained in the ambient medium (Fig. 16). Concretes of small cement content and small strength and also those with too high cement content show considerable at Fig. 19. creep. The influence of the water-cement ratio is shown. Next, the influence of the size of the element on the creep is mentioned. The phenomena during the unloading process of the concrete and for combined states of load are described in brief. Sec. 4, dealing with creep, ends with some tentative mathematical functions describing these phenomena. The following principal directions may be, discerned in the investigations of slow deformations of concrete: laboratory tests of concrete specimens, measurements of deformations of real structures and pure theoretical work. The object of generalization of these works is to elaborate a theory of concrete deformations. They are continued in many scientific centres. It encounters, however, considerable difficulties due to the number and variety of intervening parameters. The hypotheses and the theories created constitute therefore successive approximations, each of them yielding to the next one, more accurate or more general.